High-fat diet induces time-dependent synaptic plasticity of the lateral hypothalamus - Victoria Linehan; Lisa Z. Fang; Matthew P. Parsons; Michiru Hirasawa (Elsevier, 2020)
Objective: Orexin (ORX) and melanin-concentrating hormone (MCH) neurons in the lateral hypothalamus are critical regulators of energy homeostasis and are thought to differentially contribute to diet-induced obesity. However, it is unclear whether the synaptic properties of these cells are altered by obesogenic diets over time. Methods: Rats and mice were fed a control chow or palatable high-fat diet (HFD) for various durations and then synaptic properties of ORX and MCH neurons were examined using ex vivo whole-cell patch clamp recording. Confocal imaging was performed to assess the number of excitatory synaptic contacts to these neurons. Results: ORX neurons exhibited a transient increase in spontaneous excitatory transmission as early as 1 day up to 1 week of HFD, which returned to control levels with prolonged feeding. Conversely, HFD induced a delayed increase in excitatory synaptic transmission to MCH neurons, which progressively increased as HFD became chronic. This increase occurred before the onset of significant weight gain. These synaptic changes appeared to be due to altered postsynaptic sensitivity or the number of active synaptic contacts depending on cell type and feeding duration. However, HFD induced no change in inhibitory transmission in either cell type at any time point. Conclusions: These results suggest that the effects of HFD on feeding-related neurons are cell type-specific and dynamic. This highlights the importance of considering the feeding duration for research and weight loss interventions. ORX neurons may contribute to early hyperphagia, whereas MCH neurons may play a role in the onset and long-term maintenance of diet-induced obesity.